1985
DOI: 10.1037/0022-0167.32.2.272
|View full text |Cite
|
Sign up to set email alerts
|

Subjects, designs, and generalizations in Volumes 25-29 of the Journal of Counseling Psychology.

Abstract: Articles published in the Journal of Counseling Psychology (JCP), Volumes 25 through 29, were reviewed and classified in terms of (a) population from which the sample of the study was drawn, (b) the research design, and (c) the extent to which the results were generalized. A total of 424 articles were published in the five volumes. Around 70% included samples obtained from university populations. Most of the studies (394 out of 424) could be classified in one of the four research design categories offered by G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1985
1985
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Educational status of clients and therapists. The most typical clients and therapists in JCP process studies were students, supporting earlier findings by Munley (1974) and Sherman and Doan (1985). In contrast, JCCP studies more often involved clients from the community and experienced therapists.…”
Section: Characteristics Of Samplessupporting
confidence: 77%
“…Educational status of clients and therapists. The most typical clients and therapists in JCP process studies were students, supporting earlier findings by Munley (1974) and Sherman and Doan (1985). In contrast, JCCP studies more often involved clients from the community and experienced therapists.…”
Section: Characteristics Of Samplessupporting
confidence: 77%
“…This criticism, however, is not unique to this population. Ponterotto (1988) also reported an overreliance on the use of student samples in research on ethnic minorities, and Scherman and Doan (1985) reported the same to be true for all counseling research.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in regard to the trend over time, given that only eight empirical articles were specifically concerned with older adults, it is not surprising that there was no significant change in the percentage of articles published that focused on older adults over the 10-year period examined. Furthermore, despite the calls for including more older adults in the counseling literature (e.g., Buboltz, et al, 1999;Fretz, 1993;Gelso, 1985;Hanson & Mintz, 1997;Munley, 1974;Scherman & Doan, 1985), very few articles have been published in TCP and JCP with a theoretical focus on older adults. We could find evidence of only eight such articles, all of which were found in TCP.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent study of JCP, Volumes 25 to 29 (i.e., 1978-1982Scherman & Doan, 1985), documented that less than 10% of studies included participants older than traditional college age. Furthermore, older adults were not even mentioned as having been participants in any of the studies.…”
Section: Counseling Psychology and Gerontologymentioning
confidence: 99%
See 1 more Smart Citation